2008
DOI: 10.1038/nmat2205
|View full text |Cite
|
Sign up to set email alerts
|

Metallic conduction at organic charge-transfer interfaces

Abstract: The electronic properties of interfaces between two different solids can differ strikingly from those of the constituent materials. For instance, metallic conductivity-and even superconductivity-have recently been discovered at interfaces formed by insulating transition-metal oxides. Here, we investigate interfaces between crystals of conjugated organic molecules, which are large-gap undoped semiconductors, that is, essentially insulators. We find that highly conducting interfaces can be realized with resistiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
327
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(344 citation statements)
references
References 39 publications
12
327
2
3
Order By: Relevance
“…Several studies have addressed the properties of surface-supported structures involving TCNQ, where charge-transfer likewise must play a prominent role. Alves et al observed metallic conductivity within a single stacked interface of TTF and TCNQ [7]. Studies of TCNQ based salts on Au(111) surface have shown supermolecular states along the 1D TCNQ chains dependent on the geometry of neighboring molecules and hybridization with the underlying metal substrate [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have addressed the properties of surface-supported structures involving TCNQ, where charge-transfer likewise must play a prominent role. Alves et al observed metallic conductivity within a single stacked interface of TTF and TCNQ [7]. Studies of TCNQ based salts on Au(111) surface have shown supermolecular states along the 1D TCNQ chains dependent on the geometry of neighboring molecules and hybridization with the underlying metal substrate [8].…”
Section: Introductionmentioning
confidence: 99%
“…Organic electroluminescent displays and organic solar cells are already commercially available. Interfacial charge transfer makes the interface of two insulating organic crystals conductive 2 . In spintronics, organic semiconductors are regarded as attractive materials for use in spin valve devices because of their ability to maintain the spin polarization of the carriers 3 .…”
mentioning
confidence: 99%
“…Such interfaces can display remarkable properties both in inorganic 7 and organic materials. Recently, Alves et al 8 have demonstrated that metallicity can arise at the interface of two organic insulators. Here, we show that this method can also be used to significantly increase the conductivity in hybrid materials.…”
mentioning
confidence: 99%
“…Alves et al 8 already showed that charge transfer at the interface between a TTF and a TCNQ crystal can generate up to two orders of magnitude more mobile charge carriers than in FETs. Similarly, the thin film of the electron donating insulator TTF on top of the CuCl 4 -hybrid crystal introduces charge transfer at the TTFhybrid interface that increases the conductance by five orders of magnitude.…”
mentioning
confidence: 99%